2016
DOI: 10.5812/iranjradiol.22152
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Assessment of Femoroacetabular Impingement Morphology Using Computed Tomography in an Asymptomatic Young Population

Abstract: Background: Femoroacetabular impingement (FAI) is one cause of hip pain, and is an under-recognized cause of early osteoarthritis, especially in young and active people. The prevalence of FAI in adults is approximately 10 -15% and depending on the clinical and radiographic findings, two types of impingement (which are often present in combination) can be distinguished: the cam type and the pincer type. Most patients (86%) have a combination of both forms of impingement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The alpha angle is frequently used to assess cam impingement caused by femoral head asphericity and diminished femoral head–neck offset, and we considered an alpha angle > 55° abnormal, but this cut-off has not yet been firmly established in the current literature. Several authors (7,8,17,26) evaluated cam deformity by measuring AA in both the oblique axial plane and the radial plane and similarly found that the AA in the radial position revealed more abnormalities than in the oblique axial plane. Measuring only the AA in the oblique axial plane in our study may overestimate the prevalence of the cam impingement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The alpha angle is frequently used to assess cam impingement caused by femoral head asphericity and diminished femoral head–neck offset, and we considered an alpha angle > 55° abnormal, but this cut-off has not yet been firmly established in the current literature. Several authors (7,8,17,26) evaluated cam deformity by measuring AA in both the oblique axial plane and the radial plane and similarly found that the AA in the radial position revealed more abnormalities than in the oblique axial plane. Measuring only the AA in the oblique axial plane in our study may overestimate the prevalence of the cam impingement.…”
Section: Discussionmentioning
confidence: 99%
“…Teke et al. (17) found that 64.5% of the 400 joints had at least one abnormal morphological parameter associated with FAI in Turkey. At least one of the abnormal CT features was detected in 126/292 (43.2%) male hips and in 64/181 (35.4%) female hips in the Republic of Korea (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these bone abnormalities are very common in the clinical practice, and have a close relationship with femoroacetabular impingement (FAI) (4). The abnormal impact of the acetabular labral margin and the proximal femur often occurs at the end of the hip joint movement, which can be induced by certain specific positions of hip activities (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%